2020
DOI: 10.1128/jvi.01565-19
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Kaposi's Sarcoma-Associated Herpesvirus Revealed Heterogenic Replication with Dynamic Gene Expression

Abstract: Molecular mechanisms of Kaposi’s sarcoma-associated herpesvirus (KSHV) reactivation have been studied primarily by measuring the total or average activity of an infected cell population, which often consists of a mixture of both nonresponding and reactivating cells that in turn contain KSHVs at various stages of replication. Studies on KSHV gene regulation at the individual cell level would allow us to better understand the basis for this heterogeneity, and new preventive measures could be developed based on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 72 publications
(78 reference statements)
3
10
2
Order By: Relevance
“…Technical limitations such as poor sgRNA performance or number may also explain the weak signal from smaller genes such as ORF30 and ORF31, two additional components of the vTA complex. An additional limitation is that less than 25% of cells detectably express the late gene reporter (Figure S1); while this percentage is consistent with previous reports (Brulois et al, 2014;Nakajima et al, 2020), cell models allowing for more efficient late gene expression or detection should further boost the dynamic range and sensitivity. While individual sgRNAs targeting the major transactivator ORF50 behaved as expected (Figure S2b), their positive enrichment in the screen (Figure 1b,c) may represent an unknown role for ORF50 or an artifact of the screen design.…”
Section: Discussionsupporting
confidence: 87%
“…Technical limitations such as poor sgRNA performance or number may also explain the weak signal from smaller genes such as ORF30 and ORF31, two additional components of the vTA complex. An additional limitation is that less than 25% of cells detectably express the late gene reporter (Figure S1); while this percentage is consistent with previous reports (Brulois et al, 2014;Nakajima et al, 2020), cell models allowing for more efficient late gene expression or detection should further boost the dynamic range and sensitivity. While individual sgRNAs targeting the major transactivator ORF50 behaved as expected (Figure S2b), their positive enrichment in the screen (Figure 1b,c) may represent an unknown role for ORF50 or an artifact of the screen design.…”
Section: Discussionsupporting
confidence: 87%
“…We found that kaposin-deficient viruses released similar numbers of DNase-protected viral genomes to WT (Figure 5D). Although this observation suggests that the ability to package genomic material, assemble and release progeny virus does not require the kaposin locus, we and others have observed that extracellular genome copy number does not always correlate with infectious virus (21). To determine whether released virus from each kaposin-deficient latent iSLK cell line were competent to infect naïve cells, we incubated a naïve monolayer of 293T cells with supernatant from reactivated iSLK cells and 24 hours later, stained cells for the latent protein LANA.…”
Section: Resultscontrasting
confidence: 55%
“…Following reactivation, lytic gene expression follows a prescribed temporal cascade with genome replication marking the transition from early to late gene expression (19, 20). More recent analyses using single cell approaches show that lytic reactivation is quite heterogenous in terms of viral gene expression, host cell responses and outcomes (13, 2123). The lytic replication phase produces progeny virions enabling transmission of the virus and culminates in cell death.…”
Section: Introductionmentioning
confidence: 99%
“…previous reports [45,46], cell models allowing for more efficient late gene expression or detection should further boost the dynamic range and sensitivity. While individual sgRNAs targeting the major transactivator ORF50 demonstrated the expected early-stage block to lytic cycle progression ( Figs 1D, S2D, and S2E), it was surprising that they were positively enriched in the late gene screen (Fig 2B and 2C).…”
Section: Plos Pathogensmentioning
confidence: 92%